APPLICATION OF THE SUBMENTAL FLAP FOR REPAIR OF ORAL DEFECTS IN PATIENTS WITH ORAL CANCER - О. А. Saprina; М. А. Kropotov; М. V. Lomaya (Сибирский онкологический журнал)
To reconstruct defects of the oral cavity in patients with oral cancer, various displaced and free flaps are used. The paper presents the treatment outcomes of patients who underwent reconstruction of oral defects using the submental flap.